Design of Tender Management System - Alrwashdeh, Dima Farhan (2012)
One of the E-government initiatives is the development of the government-to-business (G2B) system, which is an agenda sets to promote a higher service quality between government entities and the business sector. In Jordan, the vision of E-government would be an essential and active participant in the social development and economic with ICT to enable easy access to government services and information. The tender process in Jordan will be assessing based on the capital of the enterprises in order to be tender. However, the main user is the problem of corruption in the selection of tender. This proposal is to develop tender management system for public sector in Jordan, as well as to reduce corruption. The prototype will develop by using C# language , and the research design adopted the general methodology. The evaluation was based on usability testing with the System Usability Scale (SUS) proposed by Brooke. The prototype was assessed by a sample consists of thirty eight respondents. The results have been positive; when the respondents should that they are able to use the system.